Rector’s speech / Prof. Dato’ Ir. Dr. Haji. Ahmad Rashidy Razali - Razali, Ahmad Rashidy (UiTM Global @ Office of International Affairs, 2024)
Assalamualaikum wrt wbt and greetings to all. I am honoured to be part of Universiti Teknologi MARA (UiTM) Pulau Pinang Branch’s international newsletter first edition publication. This inaugural edition, entitled ‘Global Insights: Navigating Universality with UiTM Pulau Pinang’, highlights the impactful international engagement and mobility activities between UiTM Pulau Pinang and its global partners. The edition showcases the dedicated efforts of UiTM Pulau Pinang staff and students to uphold the university’s vision of becoming a globally renowned institution by 2025 (GRU2025).